Mono-and Polyassociation Processes of Pentavalent Biotinylated PEI Glycopolymers for the Fabrication of Biohybrid Structures with Targeting Properties - Fingernagel, Johannes; Boye, Susanne; Kietz, Andre; Hoebel, Sabrina; Wozniak, Katarzyna; Moreno, Silvia; Janke, Andreas; Lederer, Albena; Aigner, Achim; Temme, Achim; Voit, Brigitte; Appelhans, Dietmar (Biomacromolecules, 2019)
This study describes new mechanistic insights in the sequential polyassociation of streptavidin with biotinylated poly(ethyleneimine) glycopolymers and biotinylated PEGylated folic acid components for the preparation of biohybrid structures (BHS) for controlled targeting experiments. Characterization of the BHS revealed that during the formation and postfunctionalization of BHS, reversible dissociation and reassociation processes occur. The BHS are stable over weeks after finalizing the equilibrium-driven polyassociation process. Cellular uptake studies showed that this sequential polyassociation involving biotinylated PEGylated folic acid components does not lead to enhanced cellular uptake of the resulting BHS. In contrast, polyplexes, containing small interfering RNA and bioconjugates (1:1 molar ratio between biotinylated glycopolymer and monomeric streptavidin-lectin fusion protein), enabled us to control the targeting of tumor cells as revealed by knockdown of the tumor-associated protein survivin. Overall, this study demonstrates the high potential of (networklike) streptavidin-biotin interactions with a dynamic character in the formation of complex BHS and extracellular matrix materials.
CRIS-Team Scopus Importer:2022-04-14